Case report of duodenal obstruction from multiple webs - Kelley Ward; Khalil A. Harbie; Saleem Islam (Elsevier, 2016)
A duodenal obstruction with three separate obstructing duodenal webs is a very rare congenital anomaly, with only one other case reported in the literature. We present a case in a 3-week-old newborn that underwent successful surgical repair.